Computational modelling of diesel engine smoke emission. - Welch, S. (Cranfield University, 1995)
This thesis is addressed to the problem of predicting the emission of exhaust smoke from the diesel engine. A simulation program based on a zonal phenomenological combustion model has been developed, permitting analysis of soot modelling techniques. For the first time, a comparative study of the common soot model expressions has been undertaken. Model sensitivities and behaviour have been critically assessed in order to determine the key model parameters and to establish a more solid predictive capability. Validation of both the combustion and soot predictions was made by means of comparison with the extensive experimental data-set of Kamimoto. The combustion model results showed a very good match between -predicted and experimental heat release curves. The only notable weakness derived from the method chosen to represent the effect of air swirl on the jet. Otherwise, the combustion predictions were deemed to be sufficiently accurate to serve as an effective platform for soot model development and analysis. The predictions of exhaust smoke for different operating conditions revealed the importance of accurately describing the overall air-to-fuel ratio in the spray. The effect of load variation was poorly represented due to neglect of the transfer of combustion products between the model zones. Soot rate predictions were generally quantitatively poor, thus requiring expression calibration. The comparative study of soot expressions identified a ranking of sensitivities of the formation expressions. Though oxidation is conceptually simpler, more distinct qualitative differences were observed in the behaviour of the expressions. The predictions of exhaust soot were found to be highly sensitive to the 'matching' of the formation and oxidation expressions over the period of the combustion process, and with poorly matched expressions, a very high sensitivity to the soot model constants was shown. The best results were obtained by use of simple quasi-chemical rate expressions.